EFFECTS OF IXERIS CHINENSIS (THUNB.) NAKAI BOILING WATER EXTRACT ON HEPATITIS B VIRAL ACTIVITY AND HEPATOCELLULAR CARCINOMA - Shih, Ko-Nien; Huang, Wen-Tao; Chang, Chung-Liang; Feng, Chih-Chung (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Background: Hepatitis B virus (HBV) infection and hepatocellular carcinoma are major diseases that affect the Taiwanese population. Therefore, the development of an alternative herbal medicine that can effectively treat these diseases is a research target. In this study, we tested Ixeris Chinensis (Thunb.) Nakai boiling water extract (ICTN BWE) in vitro and analysed its effects on the HBV and liver cancer. Materials and Methods: We used a human liver cancer cell line (Hep3B, a cell line that continuously secretes HBV particles into a medium) as an experimental model for the screening of various ICTN BWE concentrations and their effects on the HBV in vitro. Results: Our results showed that 75 µg/mL ICTN BWE downregulated the relative expression of the hepatitis B virus surface antigens (HBsAg) to 77.1%. Using the human liver cancer cell lines HuH-7 and HepG2, and 3-(4,5- dimethylthiazol-zyl)-2,5-diphenyl tetrazolium bromide (MTT) and tumour clonogenic assays, we then showed that ICTN BWE inhibits hepatocellular carcinoma growth. Conclusion: Fluorescent microscopy of DAPI(4',6-Diamidino-2-phenylindole)-stained nuclei and DNA fragmentation assays confirmed the inhibitory effects of ICTN BWE on liver tumour cell growth through induction of apoptosis.